Ecobric Sofa Making Training at MA Mamba'ul Hisan Sidayu Gresik - Warti’ah; Ahmad Afghor Fahruddin; Abdul Hakam (Indonesian Journal of Advanced Social Works, 2023)
Ecobric Sofa Making Training in MA. Mamba'ul Hisan Sidayu Gresik aims to foster creative and innovative ideas in solving the plastic waste problem. Processing plastic waste and the like into products in the form of sofas so that they have high value is the result of this training. Besides that, it can reduce plastic waste so that the environment becomes clean, healthy and comfortable.